Omega-3 PUFAs prevent bone impairment and bone marrow adiposity in mouse model of obesity - Benova, Andrea; Ferencakova, Michaela; Bardova, Kristina; Funda, Jiri; Prochazka, Jan; Spoutil, Frantisek; Cajka, Tomas; Dzubanova, Martina; Balcaen, Tim; Kerckhofs, Greet; Willekens, Wouter; van Lenthe, G Harry; et al. (Communications biology, 2023)
Obesity adversely affects bone and fat metabolism in mice and humans. Omega-3 polyunsaturated fatty acids (omega-3 PUFAs) have been shown to improve glucose metabolism and bone homeostasis in obesity. However, the impact of omega-3 PUFAs on bone marrow adipose tissue (BMAT) and bone marrow stromal cell (BMSC) metabolism has not been intensively studied yet. In the present study we demonstrated that omega-3 PUFA supplementation in high fat diet (HFD + F) improved bone parameters, mechanical properties along with decreased BMAT in obese mice when compared to the HFD group. Primary BMSCs isolated from HFD + F mice showed decreased adipocyte and higher osteoblast differentiation with lower senescent phenotype along with decreased osteoclast formation suggesting improved bone marrow microenvironment promoting bone formation in mice. Thus, our study highlights the beneficial effects of omega-3 PUFA-enriched diet on bone and cellular metabolism and its potential use in the treatment of metabolic bone diseases.
Keywords: Animals; Obesity; Humans; Fatty Acids, Omega-3; omega-3 mastné kyseliny; kosti a kostní tkáň; lidé; Bone Marrow; kostní dřeň; zvířata; Mice; obezita; Adiposity; modely nemocí na zvířatech; Bone and Bones; Disease Models, Animal; adipozita; myši